A Brief Review on the Development Progress of High-Efficiency Klystrons - Soumaya Mandal; Ayan Kumar Bandyopadhyay; Chaitali Koley; Debasish Pal; Taha Selim Ustun; Ahmet Onen (IEEE Access)
The linear beam ‘O’ type klystrons that feature very high output power (greater than several MW) with an efficiency level of 90% are considered in this study. Improvement of efficiency, which depicts the figure of merit to convert the electrical power to RF, leads to an ample amount of energy saving in the installations of particle accelerators, synchrotron radiation sources and other advanced light sources. Since the past few years, the high-performance multi-beam klystrons exhibited high efficiency by lowering perveance, but are limited to a level ~70% with an output power ~6MW.In recent years, the development of high-efficiency klystrons with peak output power exceeding 20 MW and efficiency ranges from 80-90% has been fuelled by the demand for high-energy particle accelerators. The development of mathematical and computer models of beam-wave interactions in klystrons plays a pivotal role in significantly increasing the efficiency of these devices. This paper presents a brief review on recently emerging bunching formation techniques and configurations, including the Core Oscillation Method (COM), Core Stabilization Method (CSM), Bunch Alignment Collection method (BAC), Kladistron principle, Multigap output structures, novel architecture of Two Stage Multibeam klystrons, and related optimization techniques. These techniques have been successfully adopted to achieve more than 80% efficiency in klystrons. The background theory and computer codes utilized globally are summarized in this article. Although a number of research groups are working towards enhancing the efficiency of these devices, there is an inadequacy of concise articles presenting these efforts. This article aims to address this inadequacy and also points out the challenges and the future of the high-efficiency klystrons.